Advances in functional and structural imaging of the human lung using proton MRI. (2nd July 2014) - Miller, G. Wilson; Mugler, John P.; Sá, Rui C.; Altes, Talissa A.; Prisk, G. Kim; Hopkins, Susan R.; Rizi, Rahim R.
<x xml:space="preserve">Abstract</x> The field of proton lung MRI is advancing on a variety of fronts. In the realm of functional imaging, it is now possible to use arterial spin labeling (ASL) and oxygen‐enhanced imaging techniques to quantify regional perfusion and ventilation, respectively, in standard units of measurement. By combining these techniques into a single scan, it is also possible to quantify the local ventilation–perfusion ratio, which is the most important determinant of gas‐exchange efficiency in the lung. To demonstrate potential for accurate and meaningful measurements of lung function, this technique was used to study gravitational gradients of ventilation, perfusion, and ventilation–perfusion ratio in healthy subjects, yielding quantitative results consistent with expected regional variations. Such techniques can also be applied in the time domain, providing new tools for studying temporal dynamics of lung function. Temporal ASL measurements showed increased spatial–temporal heterogeneity of pulmonary blood flow in healthy subjects exposed to hypoxia, suggesting sensitivity to active control mechanisms such as hypoxic pulmonary vasoconstriction, and illustrating that to fully examine the factors that govern lung function it is necessary to consider temporal as well as spatial variability. Further development to increase spatial coverage and improve robustness would enhance the clinical applicability of these new functional imaging tools. In the realm of structural imaging, pulse sequence techniques such as ultrashort echo‐time radial k‐space acquisition, ultrafast steady‐state free precession, and imaging‐based diaphragm triggering can be combined to overcome the significant challenges associated with proton MRI in the lung, enabling high‐quality three‐dimensional imaging of the whole lung in a clinically reasonable scan time. Images of healthy and cystic fibrosis subjects using these techniques demonstrate substantial promise for non‐contrast pulmonary angiography and detailed depiction of airway disease. Although there is opportunity for further optimization, such approaches to structural lung imaging are ready for clinical testing. Copyright © 2014 John Wiley & Sons, Ltd.